Registration of DALBG 1201 Hybrid Bluegrass. Issue 2 (16th January 2015) - Meeks, M.; Chandra, A.; Metz, S. P.; Genovesi, A. D.; Read, J. C.; White, R. H.; Miller, G.; Guertal, E.; Philley, H. W.; Sorochan, J.
Abstract : DALBG 1201 (Reg. No. CV‐101, PI 671854) is a turf‐type interspecific F1 hybrid derived from a cross between Texas bluegrass ( Poa arachnifera Torr.) 20‐11 (3‐88) (PI 655088) as the female parent and a Kentucky bluegrass ( P. pratensis L.) ecotype, CS#4, as the pollen parent. DALBG 1201 was evaluated under the designation 01‐59‐5 and TAES 5653. A total of 47 experimental hybrid bluegrass lines and three commercial checks, 'Rebel Exeda' tall fescue ( Festuca arundinacea Schreb.) and 'Reveille' and 'Thermal Blue Blaze' hybrid bluegrass ( P. arachnifera × P. pratensis ) were evaluated at five locations (Auburn, AL, Starkville, MS, Raleigh, NC, Knoxville, TN, and Dallas, TX) from 2009 to 2012. DALBG 1201 was characterized by its superior turfgrass quality, darker green color, and higher shoot density than Reveille and Thermal Blue Blaze. Its leaf texture was finer than Rebel Exeda and similar to the hybrid bluegrass checks. Linear regression analysis for turfgrass quality indicated that DALBG 1201 was more stress tolerant compared with the three commercial checks and was highly stable across varying environmental conditions. Its superior performance over a wide range of southern test locations suggests that DALBG 1201 cool‐season turf‐type hybrid bluegrass is well‐suited for use on lawns, landscapes, and other recreational sites across the southern United States.